Star turns and cameo appearances memoirs of a life among musicians - Jacobson, Bernard 1936- (University of Rochester Press, 2015)
"Star Turns and Cameo Appearances" is the entertaining and insightful memoir by veteran music critic Bernard Jacobson. Its pages are populated by eminent composers ranging from Hans Werner Henze to Andrzej Panufnik and by renowned performers, including Georg Solti, Daniel Barenboim, Sviatoslav Richter, and Jessye Norman. As a music critic and orchestra administrator, Jacobson has had the opportunity to observe these outstanding musicians and many of their colleagues at close quarters. Assisting Riccardo Muti at the Philadelphia Orchestra for eight years, he saw sides of that maestro not visible to the music-loving public. Throughout Star Turns and Cameo Performances, Jacobson adds his own sensitive and sympathetic view to public perceptions of musical luminaries of yesterday and today, helping to explain and illuminate their artistry. - Bernard Jacobson has worked in the music field for over fifty years, including stints as recording executive, music critic of the Chicago Daily News, artistic director and adviser for international orchestras in Holland, and visiting professor at Roosevelt University's Chicago Musical College. He has also performed and recorded as narrator of concert works and opera. (Klappentext)
Keywords: Jacobson, Bernard; Jacobson, Bernard -- 1936-; Music journalists -- Biography; Musicians -- Anecdotes; Biografie